RESEARCH ON THE INFLUENCE OF TECHNOLOGICAL PARAMETERS OF THE ROLLING PROCESS ON THE QUALITY OF THE SURFACE LAYER - SERDIUK, OLGA; LITVINOV, VLADISLAV; BEREZIUK, OLEG; PIVTORAC, VADUM (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The quality of the surface obtained after surface plastic deformation depends on many factors: feed, force, diameter of the roller or spool, the condition of the workpiece surface before machining and many others. This raises the question of determining the optimal machining modes, and for this it is necessary to study and evaluate the influence of factors on the quality of the surface layer. Currently, two main criteria can be considered generally accepted by which the effectiveness of surface plastic deformation of shafts is assessed for the purpose of their strengthening: the magnitude and distribution of residual stresses in the cross section, as well as the physical strengthening of the material during hardening.Since during surface plastic deformation, plastic loosening processes occur simultaneously with the hardening processes, the limiting value of the intensity of deformations should not exceed the values ​​at which the value of the used plasticity resource in the surface layer takes values ​​within 0.4…0.6.According to the modeling results, graphs were obtained that allow taking into account simultaneously the influence of changes in feed, processing effort, and workpiece rotation frequency on the resulting roughness of the part and the used plasticity resource. This allows you to choose processing modes in which it is possible to provide the specified values ​​of the roughness parameters and not exceed the used plasticity resource, and therefore obtain parts that can be operated.The feasibility of choosing the depth of the plastically deformed layer depending on the diameter of the hardened shaft in the range of 0.01 – 0.05 was confirmed, which ensures a sufficiently high efficiency of PPD in relation to fatigue strength. It is shown that the best results occur at depths close to the upper limit of the specified limit, i.e. up to 0.05. In addition, the obtained results of such modeling allow us to recommend processing modes depending on the initial roughness, the material of the part and the required roughness and hardness of the surface layer of the part
Keywords: stress; deformations; plasticity; deformation of roller; the stress-strain state